Typo Poster Traditional Medium of Communication in Epoch of Advanced Digital Technologies - Noga, Pavel (Masaryk University Press, 2020)
A typeface is one of the basic tools of human communication and for a long time a poster belonged to the most widespread means of mass communication. Upon the arrival of digital technologies it seemed that a poster would gradually disappear from the print media. However, it turns out that along with still more intensive everyday use of various text displays, there is also a renaissance of a traditional typeface poster and its extinction is probably not in sight yet.